The Influence Of Public Pressure On The Criminal Case Handling Process - Noor Asma; Arhjayati Rahim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The criminal justice system ideally aims to uphold the law fairly and objectively and avoid the intervention of external parties. If the criminal justice system is not carried out properly, it will lead to public distrust of law enforcers if the process is not fair and objective, increased insecurity if law enforcement is not carried out professionally and proportionally, resulting in public pressure on the process of handling criminal cases. The problem in this study is how the influence of public pressure on the process of handling criminal cases. The research method used is normative juridical which is carried out based on the main legal material by examining legal principles, laws and regulations, theories, concepts, and mass media news related to this research. Public pressure has a significant influence on the process of handling criminal cases. On the one hand, public pressure can encourage law enforcement to work more quickly, transparently and responsibly in handling cases. On the other hand, excessive public pressure can disrupt the legal process and hinder fair and objective law enforcement.